Efficient Design of Read Voltages and LDPC Codes in NAND Flash Memory Using Density Evolution - Chatuporn Duangthong; Watid Phakphisut; Paramote Wardkein (My University, 2023)
Low-density parity-check (LDPC) codes play an important role in the reliability enhancement of commercial NAND flash memory. Unfortunately, due to the requirement of the reading speed of NAND flash memory, the LDPC decoder will not obtain the precise soft information to achieve the performance of maximum likelihood decoding. In this work, we use a density evolution (DE) algorithm to reveal the decoding threshold of the LDPC decoder affected by the read voltages. We propose the efficient design of read voltages so that the LDPC decoder has the lowest decoding threshold. Therefore, this method can guarantee that the designed read voltages are suitable for a given LDPC code. Moreover, since we found that the designed read voltages are related to the structure of the LDPC code, the joint design of the read voltages and LDPC code is then proposed to achieve the capacity of NAND flash memory. The simulation results demonstrate that our proposed design significantly improves the frame error rate (FER) performance of NAND flash memory.
Keywords: Flash Memory; Error Correcting Code Techniques